Resource Supply Attributes Affecting Delay of High-Rise Building Construction in Thailand - Chanicha Moryadee; Bhuk Kiranantawat; Wissawa Aunyawong; Mohd Rizaimy Shaharudin (International Journal of Supply Chain Management, 2019)
Delay is one of the serious problems in the construction industry, particularly in high-rise building construction projects in Thailand. Therefore, this research aims to investigate the major causes and effects of delay problems in high-rise building construction projects in Thailand. The study employs both quantitative and qualitative study with concurrent mixed method design. Thirty-three causes and nine effects extracted from the literature review were used as the basis for further analysis. Relative Importance Index technique was used to analyse and calculate to the ranking of causes and effects of delay in Thai construction projects. The survey results were compared with the interview to unearth the true major causes of delay in Thai high-rise building construction projects. The results showed that the most significant factors of construction delay were: (1) change orders, (2) financial problem of contractor, (3) slow decision-making, (4) shortage of labour, (5) improper planning, (6) lack of good communication, (7) third party delay such as subcontractors or suppliers, (8) ambiguity of shop drawing designs, (9) shortage of construction materials and (10) late payment by owners. In terms of potential effects, the results indicated that the five most important effects were a delay in obtaining funds and profits for owners and contractors, cost overrun, time overrun, low quality due to hasty work and arbitration. Implications from these findings are further discussed.